Analysis of Factors Affecting Consumer Satisfaction of Sate Ratu Yogyakarta (Survey of Sate Ratu Consumers) - Syalehah, Ida Syahidah; Lestri, Rani Dwi; Saputri, Dhea Octavia (Asian Journal of Management Analytics, 2025)
Increasing competition in the culinary business makes culinary business people compete with each other to make a new innovation in attracting consumers. Consumer satisfaction is a problem where business actors must retain consumers with the products presented. The purpose of this study is to determine the effect of Product Quality, Price, Service Quality, Emotional Factor, Cost and Convenience on consumer satisfaction of Sate Ratu Yogyakarta. This type of research is quantitative. The population in this study is all consumers of Sate Ratu, data collection was carried out by distributing questionnaires to 100 respondents. This study used multiple linear regression analysis method with the help of SPSS.